Pengaruh Pemberian Ekstrak Daun Sambiloto Terhadap Kadar Kolesterol LDL Darah Tikus Putih (Rattus norvegicus) - Yohana Trissya Anggraeni; Jarot Subandono; . Kustiwinarni (Nexus Biomedika, 2013)
Background: Andrographis paniculata,Nes leaves contain flavonoids, beta-sitosterol, and andrographolide which can lower LDL cholesterol level of blood. The objective of this research was to determine the effect of Andrographis paniculata,Ness leaves extract against blood LDL cholesterol level of white rats (Rattus norvegicus). Methods: This study was a laboratory experimental research design, using posttest only controlled group design. Subjects of this research were white rats (Rattus norvegicus), strain Wistar, male, 3 months old, 200 grams weight. By incidental sampling technique, data were collected from 25 rats. Those rats were arranged into 5 groups, each group consisted of 5 rats. The normal control group (KKn) was administered distilled water, while the negative control group (KKn(-)) and the 1st (KP1), 2nd (KP2) and 3rd treatment group (KP3) were administered high cholesterol diet (6.25 g/kg BW/day of egg yolk). Besides that, the KP1, KP2 and KP3 were treated with 160 mg, 320 mg, and 640 mg per 200 g BW of Andrographis paniculata,Ness leaves extract, successively. This research was held for 28 days. Data of blood LDL cholesterol levels were collected 10-12 hours after the last treatment. Later, the data was analyzed by One-Way ANOVA test (? = 0.05) and Posthoc Multiple Comparisons (LSD) test (? = 0.05). Results: The one-way ANOVA test showed a significant difference among five groups p = 0.000 (p <0.05). Whereas, the LSD test showed significant differences between KKn-KKn(-), KKn-KP1, KKn-KP2, KKn-KP3, KKn(-)-KP1, KKn(-)-KP2, KKn(-)-KP3, (p < 0.05) and non-significant differences between KP1-KP2, KP1-KP3, and KP2-KP3 (p > 0.05). Conclusions Andrographis paniculata,Ness leaves extract significantly lowered blood LDL cholesterol levels of Rattus norvegicus but the increase of the dose did not enhance its function in lowering blood LDL cholesterol. Keywords: Andrographis paniculata Ness leaves extract, LDL cholesterol